Benchmarks for health expenditures, services and outcomes in Africa during the 1990s - David H. Peters; A.E. Elmendorf; K. Kandola; G. Chellaraj (The World Health Organization, 2000)
There is limited information on national health expenditures, services, and outcomes in African countries during the 1990s. We intend to make statistical information available for national level comparisons. National level data were collected from numerous international databases, and supplemented by national household surveys and World Bank expenditure reviews. The results were tabulated and analysed in an exploratory fashion to provide benchmarks for groupings of African countries and individual country comparison. There is wide variation in scale and outcome of health care spending between African countries, with poorer countries tending to do worse than wealthier ones. From 1990-96, the median annual per capita government expenditure on health was nearly US$ 6, but averaged US$ 3 in the lowest-income countries, compared to US$ 72 in middle-income countries. Similar trends were found for health services and outcomes. Results from individual countries (particularly Ethiopia, Ghana, Côte d'Ivoire and Gabon) are used to indicate how the data can be used to identify areas of improvement in health system performance. Serious gaps in data, particularly concerning private sector delivery and financing, health service utilization, equity and efficiency measures, hinder more effective health management. Nonetheless, the data are useful for providing benchmarks for performance and for crudely identifying problem areas in health systems for individual countries.